Readings in spatial patterns in space of “Bibi Fatima and the King’s sons” novel By Sheikh Dr. Sultan bin Mohammed Al Qasimi - Alkharji, Najeya Ali Rashid (Arab Journal for Sciences and Research Publishing, 2021)
This research sought to read the spatial patterns in the novel of Bibi Fatima and the sons of the king, where I began the research by defining my theory of the term space, as a general concept that includes several spatial patterns that form its general structure.Thereafter I reviewed the features of the general space in the novel, to clarify the particles that constitute it, and I was able to monitor seven spatial patterns that define the features of this space, namely: (1) voluntary places of residence- (2) places of forced residence – (3) public places of movement- (4) private places of movement- (5) movable places (6) religious place and (7) the symbolism of the place.The aim of the study is to reveal the aesthetics of geographical space in the novel, as a narrative element that contributed with other narrative elements in construction of the novel.In this study, I adhered to the technical- analytical approach, which enabled me to monitor the small particles that resemble the space of the novel, and then classify and display these spatial particles according to the importance of its contribution to the formation and progress of the events of the novel.Perhaps the most important findings I have reached was the clear susceptibility shown by the text on technical analysis; Due to the diversity of spatial forms that resemble its geographical space.I recommend more research that deals with other elements of narration in the novel, such as separation of research about the structure of time, or about the status of the narrator and the nature of his correlations.
Keywords: Novel; Space; Place; Formation; Hormuz